Protection, freedom, stigma: a critical discourse analysis of face masks in the first wave of the COVID-19 pandemic and implications for medical education - Huo, Ran; Martimianakis, Maria Athina (Canadian Medical Education Journal, 2023)
Background: The COVID-19 pandemic has spotlighted the face mask as an intricate object constructed through the uptake of varied and sometimes competing discourses. We investigated how the concept of face mask was discursively deployed during the first phase of the COVID-19 pandemic. By examining the different discourses surrounding the use of face masks in public domain texts, we comment on important educational opportunities for medical education. Method: We applied critical discourse methodology to look for key phrases related to face masks that can be linked to specific socio-economic and educational practices. We created an archive of 171 English and Mandarin texts spanning the period of February to July 2020 to explore how discourses in Canada related to discourses of mask use in China, where the pandemic was first observed. We analyzed how the uptake of discourses related to masks was rationalized during the first phase of the pandemic and identified practices/processes that were made possible. Results: While the face mask was initially constructed as personal protective equipment, it quickly became a discursive object for rights and freedoms, an icon for personal expression of political views and social identities, and a symbol of stigma that reinforced illness, deviance, anonymity, or fear. Conclusion: Discourses related to face masks have been observed in public and institutional responses to the pandemic in the first wave. Finding from this research reinforce the need for medical schools to incorporate a broader socio-political appreciation of the role of masks in healthcare when training for pandemic responses.